Nyanyian Liturgi Sebagai Pujian Manusia Atas Karya Allah; SOSIALISASI Nyanyian Liturgi dan Nyanyian Rohani Bagi Umat di Paroki Sta. Helena Camplong - Rusae, Yohanes (IPI PRESS, 2025)
Music and singing in the liturgy have a central role because they emphasize the mystery of the celebration, lead the people to appreciate the liturgical celebration and unite all the people celebrating it. Choirs preparing songs must pay attention to this important aspect in order to achieve the goals of liturgical music. Parishioners of Sta. Helena Camplong does not yet have an adequate understanding of liturgical music, especially distinguishing between types of liturgical songs and spiritual songs. As a result, the songs chosen do not comply with the rules of liturgical music. This service activity is carried out to provide an understanding of liturgical music and how to differentiate between types of liturgical songs and spiritual songs. The descriptive qualitative method is the delivery of material and training to 50 participants. The result of this activity is that the people have a correct understanding of liturgical songs (music) and spiritual songs (music) and can choose the right songs for the Eucharist.